Impact of Nature Conservation Resources of Agroecology: Insights from Hungarian Farmers and Consumer Perspectives - Annamária Harkányi; Apolka Ujj (Resources)
This study investigated the implementation of agroecological principles on three organic farms in Hungary, focusing on four resource-focused, nature conservation-related agroecological basic elements identified by the FAO: biodiversity, interactions, recycling, and resilience. This research employed a mixed-methods approach, utilising in-depth interviews as a technique to explore farmers’ practices and a questionnaire survey as a tool to assess consumer perspectives (with 63 respondents). The interviews facilitated a qualitative exploration of how agroecological practices are applied on farms, providing rich insights into the farmers’ experiences. Meanwhile, the questionnaire survey served as a structured instrument to measure consumer awareness and motivations concerning environmentally friendly farming methods. NVivo 12 software was employed for qualitative data analysis, assisting in coding and organizing responses to better understand recurring themes and patterns. The researchers found that all farms exhibited high biodiversity levels, facilitated through practices such as companion planting, crop rotation, and maintaining natural habitat patches. Agroecological farmers focus on practices suited to the landscape, fostering beneficial organisms and enhancing interactions between nature and agriculture. Integrating farm components (e.g., crops, livestock, water) promotes synergies that improve productivity and reduce reliance on external inputs. Recycling resources (like organic waste) within the farm increases efficiency, while resilience is strengthened through biodiversity, allowing farms to better withstand environmental stress. Direct marketing builds connections between producers and consumers, raising awareness of conservation practices. Consumer awareness regarding environmentally friendly agricultural practices was notably high, with findings indicating that health and ecological conservation motivations drive their purchasing decisions. This study highlights the context-dependent nature of agroecological practices, revealing that while implementation is robust, economic sustainability constraints may limit the extent to which all elements can be effectively applied. Since this research has certain limitations due to the limited sample size, expanding the study to include more farms would strengthen the findings. Nonetheless, these findings underscore the importance of integrating agroecological principles in organic farming to enhance biodiversity and foster sustainable agricultural practices.